Clinical, psychological, and physiological correlates of patients who defecate after meal. Issue 2 (February 2017) - Bouchoucha, Michel; Devroede, Ghislain; Mary, Florence; Bon, Cyriaque; Airinei, Gheorges; Bejou, Bakhtiar; Benamouzig, Robert
Abstract : Background and aims: Food is the most important synchronizer of gastrointestinal motility and secretion. Many patients with functional bowel or anorectal disorders complain of fecal urge and stool output after eating. Patients and methods: In this prospective observational study, 408 consecutive outpatients with functional bowel and/or anorectal disorders (74% female, 50.2±15.6 years, 24.8±5.0 kg/m²) filled Rome III questionnaires. Depression and anxiety scores, a physiological evaluation (total and segmental colonic transit time, colonic transit response to eating using a standard 1000 kcal test meal, and anorectal manometry), were measured. Univariate analysis and multivariate logistic regression were carried out according to the presence or not of stool output after eating. Results: Defecation after eating was found in 21% of patients. These patients were not different according to the demographic characteristics of sex ratio ( P =0.702), age ( P =0.830), and BMI ( P =0.314). In contrast, they had lower state anxiety ( P =0.032), but similar scores of depression ( P =0.240) and trait anxiety ( P =0.933). They had similar manometric characteristics (anal pressure and rectal sensitivity), but a greater response to eating in all segments of the colon. There was an increase in the frequency of functional diarrhea (odds ratio=2.576, 95% confidence interval=1.312–5.056; P =0.006) and levator ani syndrome (odds ratio=2.331, 95% confidence interval=1.099–4.944; P =0.017), but no other functional bowel disorder including irritable bowel syndrome and its subtypes was found. Conclusion: Stool output after eating is associated with clinical disorders but not physiological parameters. This symptom is not associated with irritable bowel syndrome, but a higher frequency of functional diarrhea.